The Comprehensive Systematic Review of Relationship Between Uric Acid Levels And The Risk Of Kidney Stones - Fifin Anisa (The International Journal of Medical Science and Health Research, 2026)
Introduction: Nephrolithiasis represents a significant global health burden with increasing prevalence. Although hyperuricemia has been implicated in kidney stone pathogenesis, evidence from Indonesian populations remains heterogeneous and has not been systematically synthesized. This systematic review aims to comprehensively evaluate the relationship between uric acid levels and kidney stone risk, quantify the strength of association, identify modifying factors, and address existing research gaps regarding population-specific evidence. Methods: A systematic review was conducted following standardized screening protocols. Eight electronic databases were searched for observational studies examining the association between serum/blood uric acid or dietary uric acid intake and kidney stone formation. Studies were included if they involved adult human participants (≥18 years), reported quantitative measures of association, and examined kidney stones broadly. Data were extracted regarding study design, population characteristics, uric acid measurement methods, kidney stone definition, effect estimates, and modifying factors. Results:  The proportion of kidney stone patients with elevated serum uric acid ranged from 55.3% to 66%, with mean levels between 6.7–7.3 mg/dL. Case-control studies demonstrated strong positive associations between high uric acid consumption and kidney stone risk (OR=6.756; 95% CI: 2.156–21.163; p=0.001). Dietary purine intake showed the strongest effect (OR=13.417; 95% CI: 3.042–59.171). The systematic review identified a dose-response relationship wherein nephrolithiasis risk increases progressively with rising serum uric acid levels. Age (p=0.050) and blood pressure (p=0.050) demonstrated significant associations with hyperuricemia in stone patients. Acidic urinary pH (<7) was observed in 77.1% of patients. Three studies reported no significant association, attributable to different stone type populations (calcium oxalate) versus uric acid nephrolithiasis. Discussion: This review provides the first synthesized evidence from Indonesian populations confirming hyperuricemia as a significant, dose-dependent risk factor for kidney stones, particularly among middle-aged males with metabolic comorbidities. The six- to seven-fold increased risk associated with high purine intake exceeds effect sizes reported in Western populations, suggesting possible population-specific genetic or dietary susceptibility. The dissociation between serum uric acid and urinary crystal excretion identified in one study challenges the adequacy of serum measurement alone as a risk stratification tool. Conclusion: Elevated uric acid levels are significantly associated with increased kidney stone risk in Indonesian populations, with dietary purine intake representing the strongest modifiable risk factor. Routine serum uric acid screening is recommended for adults with metabolic syndrome or family history of nephrolithiasis. Future prospective cohort studies with standardized uric acid measurement and stone composition analysis are urgently required.